Amperometric detection of D-sorbitol with NAD+-D-sorbitol dehydrogenase modified carbon paste electrode - Saidman, Silvana Beatriz (2000)
A biosensor based on modified carbon paste electrodes for the amperometric detection of D-sorbitol is described. Carbon paste electrodes were modified by D-sorbitol dehydrogenase (SDH) and nicotinamide adenine dinucleotide (NAD+) and coated with a non-conducting poly(o-phenylenediamine) (PPD) film. After partial oxidation of the immobilised NAD+ by applying a potential step f rom 0.0 to 1.2 V (SCE), the modified electrode allowed the amperometric detection of the NADH enzymatically obtained at an applied potential of 0.0 V. The resulting biosensor responded rapidly to sorbitol up to 8 x 10-4 M with a detection limit of 4 x 10-5 M.